Off the mark : how grades, ratings, and rankings undermine learning (but don't have to) - Schneider, Jack (Writer on education); Hutt, Ethan L. (Cambridge, Massachusetts ; London, England : Harvard University Press, 2023)
"Today's regimes of testing and grading satisfy only the politicians who forced them on America's schools. Yet discarding assessment also serves students poorly. Off the Mark proposes an alternative, replacing motivation-killing tests and grading systems with well-designed assessment that accurately captures learning and fosters students' potential"--
Chapter 1. How Grades Fail -- Chapter 2:\. This Is a Test -- Chapter 3. Your Permanent Record -- Chapter 4. Tools of Necessity-A Tale of Origins -- Chapter 5. The Culture of Assessment -- Chapter 6. It's a Small World After All -- Chapter 7. Home-Grown Experiments -- Chapter 8. Sustaining Learning.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 07, 2023).
JSTOR
Keywords: Grading and marking (Students); Grading and marking (Students) -- United States; Education -- Aims and objectives; Learning; Educational accountability; Education and state -- United States; Classement et notation (Élèves et étudiants); Classement et notation (Élèves et étudiants) -- États-Unis.; Apprentissage; Responsabilité du rendement (Éducation); Éducation -- Politique gouvernementale -- États-Unis.; EDUCATION / Evaluation & Assessment; Education -- Aims and objectives; Education and state; Educational accountability; Grading and marking (Students); Learning; United States; Electronic books